The Effect of Work Experience and Job Promotion on Employee Performance at PT Leetex Garment Indonesia, Majalengka Regency - Renita Sri Mulyati; Yelsha Dwi Pasca; Dini Tiara Tajriani; Eko Prasetyo (Journal of Applied Digital Business Management, 2025)
Human resources are an important factor in an organization or company. The higher the employee's ability, the higher the organizational performance. Conversely, the lower the employee's ability, the lower the organizational performance. In order for management activities to run well, employees need to have sophisticated equipment. The purpose of this research is to obtain the data and information needed to process, analyze and interpret work experience and job promotion issues that can influence employee performance. The object of this research is the employees of PT. Leetex Garment Indonesia Majalengka Regency. The research method used is descriptive and verification methods. The sample in this study was 99 respondents using the Slovin formula. Data collection techniques are by using questionnaires, interviews and observation. Data instrument testing is carried out by means of validity testing, reliability testing, data normality testing, correlation coefficient analysis, regression coefficient analysis, determination coefficient analysis, and hypothesis testing. The results of this research state that: (1) work experience at PT. Leetex Garment Indonesia in Majalengka Regency has reached more than 60% proven, namely 73% or tcount > ttable (76,786 > 1,661). (2) promotion at PT. Leetex Garment Indonesia Majalengka Regency has reached more than 60% proven, namely 76% or tcount > ttable (82,739 > 1,661). (3) employee performance at PT. Leetex Garment Indonesia Majalengka Regency has reached more than 60% proven, namely 76% or tcount > ttable (102,637 > 1,661). Work experience has a positive and significant effect on employee performance at PT. Leetex Garment Indonesia Majalengka Regency, because tcount > ttable (2,649 > 1,660). Job promotions have a positive and significant effect on employee performance at PT. Leetex Garment Indonesia Majalengka Regency, because tcount > ttable (7.161 > 1.660). From the research results, it can be concluded that discipline influences employee work performance, this is proven by the calculation results of the tcount value being greater than ttable. The amount of work experience and promotions on employee performance at PT. Leetex Garment Indonesia, Majalengka Regency, was 46.6% while the remaining 53.4% was influenced by other factors not researched by the author.